Dietary Crude Protein Levels Alter Diarrhea Incidence, Immunity, and Intestinal Barrier Function of Huanjiang Mini-Pigs During Different Growth Stages - Liu, Yating; Azad, Md. Abul Kalam; Zhao, Xichen; Zhu, Qian; Kong, Xiangfeng (Frontiers in Immunology, 2022)
Huanjiang mini-pig is an indigenous pig breed in China; however, the optimal dietary crude protein (CP) level for this pig breed during different growth stages has not been standardized yet. This study investigated the effects of different CP levels on diarrhea incidence, immunity, and intestinal barrier function in pigs. A total of 360 Huanjiang mini-pigs were assigned to three independent trials and fed the following CP diets: 5−10 kg stage, 14, 16, 18, 20, and 22%; 10−20 kg stage, 12, 14, 16, 18, and 20%, and 20−30 kg stage, 10, 12, 14, 16, and 18%. In the 5-10 kg stage, the 22% diet increased the plasma IL-1β, IL-6, IL-8, and TNF-α concentrations compared to the 14−20% diets and decreased IL-10 and TGF-β; however, these results were fluctuated in the later stages, including the decrease of IL-1β and IL-8 in the 20% group, TNF-α in the 18−20% groups, and the increase of IFN-γ in the 20% group at the 10−20 kg stage and the decrease of TNF-α in the 16% group at the 20−30 kg stage. The 20% diet increased the jejunal and ileal IL-10 concentration compared to the 14% diet at the 5−10 kg stage and the 16% diet compared to the 12% diet at the 10−20 kg stage. In addition, ileal IL-10 concentration was increased in the 16% diet compared to the 10−12 and 18% diets at the 20−30 kg stage. Furthermore, the 18% diet at the 5−10 kg stage and the 16% diet at the 10−20 kg stage decreased jejunal IL-6 expression, whereas the 20% diet increased the TNF-α and IFN-γ at the 5−10 kg stage. The 20% diet increased the Claudin, Occludin, ZO-1, ZO-2, mucin-1, and mucin 20 expression at the 5−10 kg stage, as well as TLR2, TLR4, and NF-B in the 22 and 20% diets at the 5−10 and 10−20 kg stages, respectively. Collectively, these findings suggest optimal dietary CP levels of 16, 14, and 12% for Huanjiang mini-pigs during the 5−10, 10−20, and 20−30 kg growth stages, respectively; and provide the guiding significance of dietary CP levels for Huanjiang mini-pigs during different growth stages.